1989
DOI: 10.1073/pnas.86.6.1831
|View full text |Cite
|
Sign up to set email alerts
|

Human hepatitis delta virus RNA subfragments contain an autocleavage activity.

Abstract: Hepatitis 8 virus (HDV) contains a singlestranded circular RNA genome of 1.7 kilobases. In this report we demonstrate that subfragments of HDV RNA can undergo autocatalytic cleavage. This cleavage requires at least 500 pM of Mg2+ or Ca2+, is not affected by varying the pH from 5.0 to 9.1, and occurs with RNA fragments as small as 133 nucleotides. The larger RNA fragments containing additional HDV sequences have a lower efficiency of cleavage. Deletion analysis at both ends of RNA subfragments suggested that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
202
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(209 citation statements)
references
References 22 publications
1
202
0
1
Order By: Relevance
“…Several such catalytic motifs exist, including the hammerhead, hairpin, hepatitis delta virus (HDV), the Neurospora Varkud satellite motifs, and the cofactor-dependent glmS ribozyme. [10][11][12][13][14] The HDV family of ribozymes is the topic of this chapter.…”
Section: Introductionmentioning
confidence: 99%
“…Several such catalytic motifs exist, including the hammerhead, hairpin, hepatitis delta virus (HDV), the Neurospora Varkud satellite motifs, and the cofactor-dependent glmS ribozyme. [10][11][12][13][14] The HDV family of ribozymes is the topic of this chapter.…”
Section: Introductionmentioning
confidence: 99%
“…In the next group I am placing the hepatitis D virus (HDV) ribozyme (61)(62)(63) and the TS ribozyme. Structural and mechanistic evidence indicates that the HDV ribozyme uses metal ion-bound water as the general base, and a cytosine nucleobase as a general acid (15,(64)(65)(66)(67).…”
Section: The Hammerhead Ribozyme -The Role Of a 2'-hydroxyl Groupmentioning
confidence: 99%
“…Following the discovery of the catalytic properties of RNA some 20 years ago (Kruger et al+, 1982;GuerrierTakada et al+, 1983), many more self-splicing introns belonging to two distinct groups along with three types of small self-cleaving ribozymes have been identified+ These are the hammerhead (Hutchins et al+, 1986;Prody et al+, 1986;Uhlenbeck, 1987;Verma et al+, 1997), the hairpin (Buzayan et al+, 1986;Hampel & Tritz, 1989;Hampel, 1998;Walter & Burke, 1998), and the delta ribozymes (Sharmeen et al+, 1988;Wu et al+, 1989)+ Two types of reactions are mediated by these ribozymes, namely RNA splicing and site-specific RNA cleavage (Cech, 1987)+ In the case of the three above classes of self-cleaving ribozymes, the autolytic processing reaction proceeds with inversion of configuration of the phosphate group, as initially established with hammerhead-type ribozymes (van Tol et al+, 1990;Koizumi & Ohtsuka, 1991;Slim & Gait, 1991)+ A general feature of ribozymes is that they either require or are at least stimulated by divalent metal cations (Dahm & Uhlenbeck, 1991;Dahm et al+, 1993)+ Many of the natural ribozymes show rather broad metalion specificity+ Thus, hammerhead-type ribozymes are active with several earth alkali cations (Mg 2ϩ , Ca 2ϩ , Sr 2ϩ ) or transition metal cations (Mn 2ϩ , Co 2ϩ , Zn 2ϩ ) (Dahm & Uhlenbeck, 1991)+ Detailed analysis of the metal-ion dependence of cleavage reactions mediated by ribozymes provides evidence that the precise role of the metal ions varies considerably between different classes of ribozymes+ For example, RNA catalysis in the case of the hairpin ribozyme does not involve direct coordination of magnesium to the phosphate ester, nor activation of a bound water molecule, as demonstrated by efficient pH-independent cleavage in the presence of cobalt hexammine (Hampel & Cowan, 1997;Nesbitt et al+, 1997;Young et al+, 1997;Fedor, 2000)+ In addition, it was shown that aminoglycoside antibiotics or spermine alone can promote efficient hairpin cleavage with rates similar to the magnesium-dependent reaction (Earnshaw & Gait, 1998)+ Similarly, the Hepatitis delta virus ribozyme does not require high concentrations of metal ions for activity, perhaps due to a particular cytosine that could act as the general base in the cleavage reaction (Ferré-D'Amaré et al+, 1998;…”
Section: Introductionmentioning
confidence: 99%